Mental health professionals' (AMHPs) perspectives on interpreter-mediated mental health act assessments - Young, Alys; Vicary, Sarah; Tipton, Rebecca; Rodríguez Vicente, Natalia; Napier, Jemina; Hulme, Celia; Espinoza, Francisco (Journal of social work : JSW, 2024)
Summary This article concerns interpreter-mediated Mental Health Act (MHA) (1983) assessments where either a signed or spoken language interpreter is required. It reports data from 132 Approved Mental Health Professionals (AMHPs) in England who have direct experience of such circumstances addressing expertise, training, readiness, and potential influences on the outcome when interpreters are involved. Quantitative data were collected by means of an online survey analyzed descriptively with additional open-ended qualitative responses analyzed thematically. Findings More interpreter-mediated MHA assessments were reported as occurring in hospital than in community settings. Although AMHPs were confident in their expertise, nearly two-thirds felt they were less effective when an interpreter was involved. The vast majority had received only minimal training on how to work with an interpreter. Recording of language and interpreter use in the assessment was revealed as inconsistent. Most AMHPs thought incorrectly that interpreters were subject to mandatory registration with assured minimum standards of qualification and expertise. Practical problems associated with the timeliness of access to interpreters and complexities of using telephone interpreters instead of face to face were raised. AMHPs expressed a wish for more training and guidance including expectations of the interpreter role. Applications Consistent standards of formal recording of interpreter use as part of annual monitoring of the MHA are required to understand any potential inequities of outcome resulting from language mediation. Joint training with interpreters is desirable with more specific guidance and resources for working AMHPs and interpreters to promote best practice.